Handbook of technical communication - Mehler, Alexander, 1967-; Romary, Laurent; Gibbon, Dafydd (Handbooks of applied linguistics ;, 2012)
The Handbook of Technical Communication brings together a variety of topics which range from the role of technical media in human communication to the linguistic, multimodal enhancement of present-day technologies. It covers the area of computer-mediated text, voice and multimedia communication as well as of technical documentation. In doing so, the handbook takes professional and private communication into account. Special emphasis is put on technical communication by means of web 2.0 technologies and its standardization in system development. In summary, the handbook deals with theoretical issues of technical communication and its practical impact on the development and usage of text and speech technologies.